2019
DOI: 10.4081/ijfs.2019.7724
|View full text |Cite
|
Sign up to set email alerts
|

Quality parameters of hunted game meat: Sensory analysis and pH monitoring

Abstract: The aim of the present research is to propose a new, quick and objective method for the certification of hunted and/or culled wild game meat quality and to monitor its origin and the hunting practices adopted by hunters. The expected deliverable is a new labelling scheme for Italian hunted wild game meat that will guarantee high quality and safety standards for consumers and will decrease transaction costs of the supply chains. During the 2015, 2016 and 2017 hunting seasons, 1,056 hunted wild ungulates were sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 18 publications
2
28
0
Order By: Relevance
“…Furthermore, hunters agreed that the processing practices carried out after killing on the hunted wild boar involve higher health and hygiene risks related to incorrect on-site game dressing. In fact, untrained hunters might compromise the quality of game meat mainly due to errors during evisceration, resulting in bacterial contamination, or suboptimal bleeding operations, impeding the correct acidification of meat [ 4 ]. As shown in Figure 3 all the investigated statements revealed statistically significant differences between the two supply chains ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, hunters agreed that the processing practices carried out after killing on the hunted wild boar involve higher health and hygiene risks related to incorrect on-site game dressing. In fact, untrained hunters might compromise the quality of game meat mainly due to errors during evisceration, resulting in bacterial contamination, or suboptimal bleeding operations, impeding the correct acidification of meat [ 4 ]. As shown in Figure 3 all the investigated statements revealed statistically significant differences between the two supply chains ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, hunters agreed that the processing practices carried out after killing on the hunted wild boar involve higher health and hygiene risks. In fact, according to the literature, the evisceration and bleeding are the most critical on-site dressing operations on games and involve bacterial contamination risks and potential deterioration of the meat quality due to muscle acidification issues [ 4 ]. These results show that hunters evaluate themselves in a negative way, in particular owing to the final phases of the production process, reporting overall that they do not trust their own product and consider a product deriving from farmed meat more reliable and safer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, data suggest that the muscle tenderness of Yunling cattle was better than that of Simmental cattle. Various biochemical reactions still exist in muscle postmortem but mainly anaerobic metabolism, constantly generating plenty of lactic acids and other substances, resulting in decreased pH value in muscle (32,33). It was found that the tenderness of muscle was the highest at the beginning of slaughter and then reduced along with the decrease of pH.…”
Section: Discussionmentioning
confidence: 99%
“…Given these characteristics, hunted game meat can also be considered more environmentally friendly than the meat obtained by the intensive livestock farming system, if obtained under strict and regulated hunting practices of course (Ljung et al 2012;Nielsen 2016). More specifically, the public appears to find hunting practices more acceptable if they have some purpose (Gamborg and Jensen 2017), as in the case of the remarkable demographic increase in Italy of red deer and wild boar, which is often considered more of a problem than a resource (Vigan o et al 2019).…”
Section: Introductionmentioning
confidence: 99%